Small and slow is safe: On the drought tolerance of tropical tree species. (20th January 2022) - Guillemot, Joannès; Martin‐StPaul, Nicolas K.; Bulascoschi, Leticia; Poorter, Lourens; Morin, Xavier; Pinho, Bruno X.; le Maire, Guerric; R. L. Bittencourt, Paulo; Oliveira, Rafael S.; Bongers, Frans; Brouwer, Rens; Pereira, Luciano; et al.
Abstract: Understanding how evolutionary history and the coordination between trait trade‐off axes shape the drought tolerance of trees is crucial to predict forest dynamics under climate change. Here, we compiled traits related to drought tolerance and the fast‐slow and stature‐recruitment trade‐off axes in 601 tropical woody species to explore their covariations and phylogenetic signals. We found that xylem resistance to embolism (P50) determines the risk of hydraulic failure, while the functional significance of leaf turgor loss point (TLP) relies on its coordination with water use strategies. P50 and TLP exhibit weak phylogenetic signals and substantial variation within genera. TLP is closely associated with the fast‐slow trait axis: slow species maintain leaf functioning under higher water stress. P50 is associated with both the fast‐slow and stature‐recruitment trait axes: slow and small species exhibit more resistant xylem. Lower leaf phosphorus concentration is associated with more resistant xylem, which suggests a (nutrient and drought) stress‐tolerance syndrome in the tropics. Overall, our results imply that (1) drought tolerance is under strong selective pressure in tropical forests, and TLP and P50 result from the repeated evolutionary adaptation of closely related taxa, and (2) drought tolerance is coordinated with the ecological strategies governing tropical forest demography. These findings provide a physiological basis to interpret the drought‐induced shift toward slow‐growing, smaller, denser‐wooded trees observed in the tropics, with implications for forest restoration programmes. Abstract : We compiled traits related to drought tolerance and the fast‐slow and stature‐recruitment trade‐off axes in 601 tropical woody species to explore their covariations and phylogenetic signals. Overall, our results imply that: (1) drought tolerance is under strong selective pressure in tropical forests, and TLP and P50 result from repeated evolutionary adaptation of closely related taxa; and (2) drought tolerance is coordinated with the ecological strategies governing tropical forest demography: slow and small species tend to be more tolerant to drought.